Pengaruh Ukuran Perusahaan, Leverage, dan Profitabilitas Terhadap Manajemen Laba - Yolanda Pratami; Didit Pradipto (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
This study aims to examine the effect of firm size, leverage, and profitability on earnings management. The dependent variable used is earnings management, and the independent variables used are firm size, leverage, and profitability. The subjects of this research are pharmaceutical sector companies listed on the Indonesia Stock Exchange 2017-2019. This sample was selected using a purposive sampling method. The total sample used is 10 sample data. This research method uses multiple linear regression analysis which is processed using spss 25. The results of this study simultaneously show that firm size, leverage, and profitability have an effect on earnings management. Based on the results of the determination test which shows the value of the coefficient of determination is 0.406. These results indicate the ability of the independent variable to explain the dependent variable by 40.6%, while the remaining 59.4% is explained by other variables. While partially shows that firm size and profitability have a positive and significant effect, while leverage has a negative and significant effect on earnings management. Keywords: Firm Size, Leverage, Profitability and Earnings Management.